Changing demographics in India's Northeast and its impact on security - Gupta, Ashwani (KW Publishers Pvt. Ltd. Centre for Land Warfare Studies, 2016)
Northeast India is a unique mix of ethnic, cultural, religious and linguistic diversity. The British policies of the 19th and 20th centuries encouraged movement of settlers into Assam and Bengal for increasing productivity and reclaiming barrer tracts of land. This uncontrolled movement was resented by the tribal population, who feared loss of their land and identity